Continuous Improvement Model under the Lean Six Sigma and KPIs approach to reduce unproductive times in the loading and hauling stage in surface mining - Vallejo, Angelica Alexia Da Silva (2023)
This article shows us how the Lean Six Sigma (LSS) methodology, within the operational management of small and medium-sized mining companies, promotes the development of a new evaluation method aimed at reducing unproductive times in one or more operations. However, this study only seeks to implement this methodology in the stages of cleaning, hauling, and transportation. While Lean and Six Sigma methodologies are different tools, they are often combined to reduce waste, non-value-added activities, and process variability in order to achieve desired levels of operational efficiency. This work provides useful and significant information to unveil the maximum value obtained from the implementation of the LSS methodology in the development of this new method, as it not only provides a comprehensive diagnosis of the evaluated operations but also a quantitative estimation of the potential improvement levels that could be achieved if implemented correctly.